PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Pada Hotel Ratu Mayang Garden Pekanbaru) - Apandi Saputra; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the Effect of Work Environment and Organizational Commitment on Employee Satisfaction (Case Study at Hotel Ratu Mayang Garden Pekanbaru). Work Environment as a variable (X1) Organizational Commitment as a variable (X2) and Job Satisfaction as (Y).The method in this research is descriptive and quantitative by using SPSS 20 program. The sample used is 92 employees consisting of 10 departments. To determine the sample using census research method. Technique of collecting data through questionnaire.The results of analysis using multiple linear regression, t test, and test f. It can be seen that the Work Environment has significant effect on Employee Satisfaction, Organizational Commitment has a significant effect on Employee Job Satisfaction, and Work Environment and Organizational Commitment have a significant effect on Employee Satisfaction.Keywords: Work Environment, Organizational Commitment, Job Satisfaction.